TINDAKAN SOSIAL KH. MUHAMMAD BAKHIET DALAM KONTEKSTUALISASI DAN TRANSFORMASI AJARAN TASAWUF - Sulaiman Kumayi (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
The article is a result of qualitative research that focuses on understanding data by means of classification, categorization, and taxonomy; while the approach in this research is Max Weber’s Social Action Theory to analyze Guru Bakhiet’s Sufism thought with the perspective of Max Weber’s social action theory. By referring to Weber’s theory, Guru Bakhiet occupies the position as ‘the actor/agent, the meaning, and the movement.’ As the actor, he is ‘the source of meaning, the interpreter of meaning, and contextualizing and transforming meaning’ to his own community or outside community so that they are moved to act. He builds his movement with a rational action based on the value. The value of his central reference is the teachings of Sufism that have been interpreted creatively to be understood by others and act with and on behalf of the value. Therefore, the movement or social action is performed by Guru Bakhiet is not merely emerges from a vacuum. It appears in an interaction pattern that already exists between individuals and groups. Therefore, when Sufism in his mind, it means the actor speaks of texts, while the texts are about language, and the language plays the personality of the Sufis and the people around them. Because of his important role, it is very important to continue to renew the language of Sufism and refresh it in order to maintain its transformative power or social criticism in the contextual or reality realm.